The Role of Networking Behavior in the Internationalization of Turkish Firms - Bozbeyli, Derin; Srivastava, Mohit; Ryška, Tomáš, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This study examines the role of networking behavior in the internationalization of Turkish firms. The goal of this study is to answer the question: What kind of an influence does the networking behavior of Turkish firms have on the uncertain environment, which the firms face during the process of foreign market entry? The data, which is collected from 56 respondents, is analyzed with the first model of the moderator analysis. The findings show no support for the claim that networking increases the performance of the firms through reducing the uncertainty. However the findings supports the claim that the networkingincreases the performance of the firms independently from the uncertainty.
Vedoucí práce: Mohit Srivastava
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses